QUALITY OF MUDHARABAH AND MURABAHAH FINANCING TO INCREASE BANK MANDIRI SYARIAH'S PROFITS - Siddiq, Fajar (Journal Of Sharia Banking, 2024)
The quality of mudharabah and murabahah financing to increase Bank Mandiri Syariah's profits is an important study to explore. The aim of the research is to determine the development of mudharabah and murabahah financing products at Mandiri Syariah Banks, to determine and analyze profit growth at Mandiri Syariah Banks, and to describe the role of profit sharing and buying and selling agreements in increasing profits at Syariah Banks. This type of research is quantitative descriptive research. Quantitative descriptive research explains the position of the variables studied and the relationship between one variable and other variables. In this study there are 3 variables consisting of mudharabah financing (X1), murabahah financing (X2), as the independent variable and sharia bank net profit (Y) as the dependent variable. Bank Syariah Mandiri has made improvements to mudharabah and murabahah financing products from 2016 to 2019 experienced positive growth in assets, equity (capital) and net profit. Bank Mandiri Syariah is able to manage assets, financing, third party funds and equity well, which is then reflected in significant profit growth. Meanwhile, mudharabah and murabahah contracts increase Bank Mandiri Syariah's profits. Bank Syariah Mandiri has succeeded in increasing its mudharabah and murabahah financing products from 2016 to 2019. Previous research shows that Bank Mandiri Syariah recorded significant growth in its mudarabah and murabahah loan products as well as other financial performance aspects such as net profit, assets, and equity capital.